Diversity of Mushroom Coral (Fungidae) in Siladen Waters, North Minahasa - Bambang Hermanto (Sam Ratulangi University, 2013)
Mushroom coral are well known in the waters of southeast asia because in this region has encountered in high abundance in shallow water and reef slope. Research on the diversity of mushroom coral (Fungiidae) conducted in July in the sea of Siladen island with four observation stations, they are Siladen I, Siladen II, Siladen III and Siladen IV. The research aims to determine mushroom coral species and diversity in the sea of Siladen Island, North Minahasa. This research use belt transect method and be extends parallel of the shoreline with 50x3m length of transects. The results showed that 13 species from seven genera were recorded. They are Fungia, Heliofungia, Ctenactis, Herpolitha, Polyphyllia, Sandalolitha and Podabacia. The number of coral species are found in the sea of Siladen island reached 32% of all coral species in the tropical Indo-Pacific region. Diversity Index of mushroom coral in the Siladen waters ranged from 0.837–0.97. Mushroom coral density each station ranged from 0,11-0,22 ind/m2.Keywords : Diversity, mushroom coral, Siladen Island, North Minahasa